Forskarinitierat rollspel med efterföljande fokusgruppintervju - Jenny Rendahl; Signild Risenfors; Peter Korp; Marianne Pipping Ekström; Christina Berg (Educare)
Role-play is a useful pedagogic tool because it involves active participation and facilitates various ways of expression. However, role-play has received less attention as a research method. We have used researcher-initiated role-play with subsequent focus group interview in a study of adolescents' conceptions about food messages. In this paper we will use our experiences from this empirical study to describe and evaluate the use of researcher-initiated role-play with subsequent focus group interview as a method for data collection. In our empirical study the participants chose and played role characters representing agents they think convey food messages to them in their everyday life. They planned, bought, cooked and ate the food, and after that they participated in a focus group interview. Our experience is that this method enables participants to be active throughout the research process. They influence how the role-play proceeds, which diverts the control from the researcher to the participants and reduces the power hierarchy. Furthermore, this method promotes reflection among the participants. Both because they are acting in roles and because they are confronted with interaction with authentic food. In our study this contributed to a rich data material. Therefore, we consider this method to be a promising research method for studies concerning everyday practices.